Color and material for hotel interior / Syed Abdul Malek Syed Ziad Wapha - Syed Abdul Malek, Syed Ziad Wapha (Faculty of Architecture,Planning and Surveying, 1992)
The - F i r s t t h i n g most p e o p l e n o t i c e upon e n t e r i n g a s p a c e i s t he c o l o u r scheme,because the c o l o u r c r e a t e s impact and a t m o s p h e r e . T h e r e are t h e warm c o l o u r s l i k e r e d , o r a n g e , t a n , g o l d,p i n k and y e l l o w which can be used t o make even .the c o l d e s t space seems, warm and c o s y , and a t t h e o t h e r end of t h e s c a l e t h e r e are the cool or p o s i t i v e l y c o l d c o l o u r s such as b l u e s , g r e e n s, 1 i l a c s , p u r p l e s , s o m e greys and t u r q u o i s e . T h e s e can h e l p t o c r e a te a s p a c i o u s , e l e g a n t l o o k < i f t h e y a r e n o t t o o d a r k ) i n a r e l a t i v e lys m a l l area. A t h i r d group o-f c o l o u r s a r e o-ften c a l l e d " n e u t r a l".and i n c l u d e g r e y s (those w i t h same c o l o u r c o n t e n t ) , b e i g e s , c r e a ms and o-f-F w h i t e s , a l t h o u g h s t r i c t l y s p e a k i n g t h e o n l y r e a l n e u t r a ls a r e pure black and w h i t e , o r a m i x t u r e o-F them i n v a r y i ng q u a n t i t i e s to c r e a t e a t r u e g r e y . T h i s range can be used .most s u c c e s s f u l l y to c r e a t e a b a l a n c e between s e v e r a l .strong or contrasting colours , oralon e f o r a s o p h i s t i c a t e d t o n e - o n - t o n e or m o n o c h r o m a t i c scheme.